Mountain Adventure Tourism: The Effect of Personal Values, Participation Constraints and Tourist Amenities Toward Tourist Satisfaction - NAHARIA, Azizah; LISTYORINI, Haniek (Journal of Tourism Economics and Policy, 2025)
The natural beauty of Indonesia which is in the position of the ring of fire causes many mountain clusters on various islands in Indonesia, this increases the interest and activities of mountain climbing, especially among young people. This study aims to analyse the factors that cause the satisfaction of mountaineering tourists both in terms of personal values, obstacles and amenities provided by the manager of mountaineering activities. The research method was carried out with a quantitative method approach by distributing questionnaires to mountaineering communities throughout Indonesia as many as 100 respondents. The results of the questionnaire were processed with SMART PLS-4. The results of the study show that the personal value and amenities provided for climbers will increase tourist satisfaction, on the other hand, obstacles both in health, skills and risks have a negative influence on the satisfaction of mountaineers. This implies that as a special interest tourist, a mountaineer needs to have strong personal values and provide with adequate amenities, and improving in their health and skills to be able to overcome risks in order to feel satisfaction in mountaineering activities.